Pengembangan Kemampuan Menulis Best-Practice Report Guru MTs. Miftahulfalah Bandung - Hidayat, Asep; Syaodih, Erliany; Budilestari, Puji; Mariam, Popon (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2020)
The problem faced by MTs Miftahulfalah teachers is the difficulty of implementing reflective actions to improve the quality of learning. The solution to the problem using assistance with the design thinking approach in (1) reflecting on the learning that has been carried out; (2) utilizing the results of reflection to improve and develop learning in the subjects being taught; and (3) conducting classroom action research to improve the quality of learning in the subjects being taught. The method used in the form of mentoring groups of two-three teachers by one lecturer, carried out using the Design Thinking Approach with three blocks of input-process- output activities. The results achieved in the form of increasing teacher knowledge and skills in (1) taking reflective action, starting from analyzing the difficulties and learning problems, finding the actions needed to overcome them, making an action plan as outlined in the lesson plan; (2) implementing class actions in accordance with the RPP made; and (3) compiling a best-practice report that contains the best experiences of teachers overcoming learning difficulties, and scientific articles as a means of sharing experiences with other teacher peers.